2017
DOI: 10.1016/j.jcss.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and performance evaluation of stealthy false data injection attacks on smart grid in the presence of corrupted measurements

Abstract: The false data injection (FDI) attack cannot be detected by the traditional anomaly detection techniques used in the energy system state estimators. In this paper, we demonstrate how FDI attacks can be constructed blindly, i.e., without system knowledge; including topological connectivity and line reactance information. Our analysis reveal that existing FDI attacks become detectable (consequently unsuccessful) by the state estimator if the data contains grossly corrupted measurements such as device malfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…C9. Security Intrusion detection ( [8], [15], [52], [74], [76], [77], [143], [148], [209]),false data injection attacks ( [13], [16], [17], [31], [100], [119], [151], [163], [168], [184], [185], [230], [251], [257]), energy theft ( [54], [99], [169], [191], [254], [258]), distinguishing cyber-attacks from physical faults ( [18])…”
Section: Sms Resultsmentioning
confidence: 99%
“…C9. Security Intrusion detection ( [8], [15], [52], [74], [76], [77], [143], [148], [209]),false data injection attacks ( [13], [16], [17], [31], [100], [119], [151], [163], [168], [184], [185], [230], [251], [257]), energy theft ( [54], [99], [169], [191], [254], [258]), distinguishing cyber-attacks from physical faults ( [18])…”
Section: Sms Resultsmentioning
confidence: 99%
“…A detection method was established for false data injection (FDI) based on extended distributed state estimation . Anwar et al (2016) revealed that existing FDI attacks become detectable by the state estimator if the data contains grossly corrupted measurements such as device malfunction and communication errors. The information security should become one of the most important topics in the future energy system research field.…”
Section: Resultsmentioning
confidence: 99%
“…3. Studies [6,[40][41][42][43] have proven that cyber attacks can happen on both uplinks and downlinks. Owing to different types of attacks (such as DoS attack, uplink spoofing attack, downlink spoofing attack), the influence of ECPSs is different.…”
Section: Attack Scenariosmentioning
confidence: 99%